Opioid receptors reveal a discrete cellular mechanism of endosomal G protein activation - Nicole M. Fisher; Mark von Zastrow (Proceedings of the National Academy of Sciences, 2025)
Many GPCRs initiate a second phase of G protein-mediated signaling from endosomes. This inherently requires the GPCR to increase cognate G protein activity on the endosome surface. G s -coupled GPCRs are thought to achieve this by internalizing and mediating a second round of allosteric coupling to G proteins on the endosome membrane. Here, we provide evidence that the μ-opioid receptor (MOR), a G i -coupled GPCR, is able to increase endosomal G protein activity in a different way. Leveraging conformational biosensors, we show that MOR activation triggers a transient increase of active-state G i/o on the plasma membrane that is followed by a prolonged increase on endosomes. Contrary to the G s -coupled GPCR paradigm, however, we show that the MOR-induced increase of active-state G i/o on endosomes requires neither internalization of MOR nor the presence of activated MOR in the endosome membrane. We propose a distinct and additional cellular mechanism of endosomal signaling by G i/o that is communicated through trafficking of the activated G protein rather than its activating GPCR.